Effects of decomposing cadavers on soil nematode communities over a one-year period. (December 2016) - Szelecz, Ildikó; Sorge, Franziska; Seppey, Christophe V.W.; Mulot, Matthieu; Steel, Hanne; Neilson, Roy; Griffiths, Bryan S.; Amendt, Jens; Mitchell, Edward A.D.
Abstract: In terrestrial ecosystems decomposing cadavers act as resource patches affecting nutrient cycling and soil communities, but the effects on soil communities are not well known. In this study we investigated nematode community response to decomposing pig cadavers ( Sus scrofa ) over a one-year period. As nematodes play key roles in soil food webs and are known to respond to disturbances and nutrient enrichment, we hypothesised that they would respond to decomposing cadavers and that this response would change over time. We compared the temporal patterns of nematode density and community structure under pig cadavers, either placed directly on the ground or hung 1 m aboveground (for effects of cadaveric fluids only), with two controls, i.e., bare soil and bags filled with soil placed on the ground (fake pigs – for microclimatic effects only). In the control and fake pig treatments nematode densities, community patterns and maturity indices did not change significantly. In contrast, density increased significantly underneath the ground and hanging pigs two weeks after the beginning of the experiment, and nematode family richness, Simpson diversity and maturity index were significantly reduced in the cadaver treatments. Most nematode families responded negatively to cadavers with the notable exceptions of Rhabditidae, Neodiplogasteridae and Diplogasteroididae. The latter two were found exclusively underneath the decomposing cadavers and are promising bioindicators of vertebrate cadaver decomposition. Even though diversity, density and communities were recovering after one year, the impact of cadavers was still significant for the maturity index. These contrasting patterns illustrate how decomposing cadavers contribute to increasing local biodiversity and suggest that soil nematodes could be used as a tool to document the presence of a decomposing cadaver, or to estimate the time elapsed since death (post-mortem interval). Patterns should, however, be compared in different settings and seasons before such a tool can be validated. Highlights: The abundance of bacterivorous nematodes increased during cadaver decomposition. Additional bacterivorous and predacious nematodes were attracted. Decomposing cadavers alter local nematode diversity. Recovery of nematode communities started in the final decomposition stages. Three nematode families reflecting the decomposition process are possible bioindicators.